Grammatical Music Composition with Dissimilarity Driven Hill Climbing - Loughran, Róisín; McDermott, James; O’Neill, Michael (Evolutionary and Biologically Inspired Music, Sound, Art and Design, 2016)
An algorithmic compositional system that uses hill climbing to create short melodies is presented. A context free grammar maps each section of the resultant individual to a musical segment resulting in a series of MIDI notes described by pitch and duration. The dissimilarity between each pair of segments is measured using a metric based on the pitch contour of the segments. Using a GUI, the user decides how many segments to include and how they are to be distanced from each other. The system performs a hill-climbing search using several mutation operators to create a population of segments the desired distances from each other. A number of melodies composed by the system are presented that demonstrate the algorithm’s ability to match the desired targets and the versatility created by the inclusion of the designed grammar.